PENGARUH PROGRAM TALKSHOW INDONESIA LAWYERS CLUB TERHADAP PEMBELAJARAN HUKUM MAHASISWA FAKULTAS HUKUM UNIVERSITAS RIAU - Anggraini, Kiki; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The mass media is currently growing rapidly along with the development of technology. The development of mass media to support people to access the latest information in order to meet the human need for information, the power of television as a medium that is frequently accessed by the public, many programs are varied and interesting served by television stations to attract audiences to consume a program that has been at the ready. One of them is the talk shows Indonesia Lawyers Club are broadcast by television stations AFP. Talkshow Program Indonesia Lawyers Club is a program as News Talk show in containers are Interactive and slick to provide learning for viewers Law. Indonesia Lawyers Club events program is always the keynote speakers - the main speaker and see an issue from different perspectives. In theory S-O-R (Stimulus - Organism - Response) media directional effect, immediately and directly to the communicant. The purpose of this study is to determine whether there is influence between Talkshow Program Indonesia Lawyers Club of the Education Faculty of Law, University of Riau. The method used in this research is quantitative method. Data collection techniques in this study using a questionnaire. The number of samples for this study were 60 respondents. Sampling using simple random sampling method. To determine the influence of these two variables, the researchers used a simple linear regression analysis. For the processing of questionnaire data, were performed using the Statistical Product And Service Solution (SPSS) Windows version 17. Results of research on the effect of Indonesia Lawyers Club Talkshow Program Against Education Law Faculty of Law, University of regression coefficient values obtained in this study is Y = 0.930 + 0.659 X 0.000 with a significance level of less than Î± = 0.05. This means that there are significant Talkshow Program Indonesia Lawyers Club Against Education Law Faculty of Law, University of Riau amounted to 57.4% and in the category of Medium effect. These percentages show that Talkshow Program Indonesia Lawyers Club there is an influence on the learning of Law Faculty of Law, University of Riau. Thus H0 is rejected and Ha accepted.